Geoengineering and geographers: Rewriting the Earth in what image?. Issue 3 (9th September 2018) - Bellamy, Rob; Palmer, James
Abstract : Large‐scale intervention in the Earth's climate system features centrally both in definitions of, and proposed responses to, the Anthropocene. In its deliberate guise – as climate geoengineering – such intervention is highly contentious, threatening to profoundly reshape the geography and politics of environmental governance frameworks, not to mention the nature of the environments towards which those frameworks are oriented. Yet, even as experiments with geoengineering technologies are growing in number, geographers continue to engage seldom with scientific, political or indeed public debates about them. In this paper we contend that geographical ideas about space, scale, power and geopolitics must urgently be brought to bear on ongoing efforts to experiment with geoengineering, and to deliberate its future role in responses to climate change. We develop this argument in two parts. First, we suggest that ongoing debates about the acceptability of geoengineering experimentation would benefit from recognising incumbent spatial and scalar categorisations (e.g., small scale vs. large scale, indoors vs. outdoors) not as fixed ontological anchors, but as relational and provisional constructs, open to being rethought in new, potentially productive ways. Second, we call for geographers to document and contest inequalities and injustices, both in debates about what geoengineering is or might become, and in the outcomes generated by efforts to undertake geoengineering in practice. Here there are opportunities for geographers to reshape the frames of reference used by others to comprehend the implications of the Anthropocene itself, drawing on traditional disciplinary strengths in ecofeminism, political ecology and environmental justice, as well as the production of space and critical geopolitics. Such endeavours, we contend, will form a vital complement to existing geographical engagements with the concept of the Anthropocene, reaffirming the value of the discipline's distinctive – and explicitly normative – voice within ongoing policy and public deliberations.